2019
DOI: 10.2106/jbjs.rvw.18.00056
|View full text |Cite
|
Sign up to set email alerts
|

Markers for Malnutrition and BMI Status in Total Joint Arthroplasty and Pharmaconutrient Therapy

Abstract: Evaluating the nutritional status of an orthopaedic patient prior to total joint arthroplasty can offer insight into potential postoperative outcomes.» Laboratory values, such as total lymphocyte count, serum albumin, and serum prealbumin, anthropometric measurements, and screening tools are all important resources in assessing nutritional status.» Using body mass index (BMI) in conjunction with laboratory values and other resources to adequately assess nutritional status can be effective in predicting outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 68 publications
(78 reference statements)
0
26
0
Order By: Relevance
“…One study found that interview-based screening tools performed preoperatively in hospitalized TJA patients, including the Nutritional Risk Screening (NRS 2002), Mini Nutritional Assessment (MNA), and Short-Form Mini Nutritional Assessment (SF-MNA), were able to predict risks of prolonged hospitalization, delayed mobilization, quality of life, and adverse events postoperatively [37]. In particular, the MNA has been shown to have a significant association with serum albumin and increased length of stay [67].…”
Section: Resultsmentioning
confidence: 99%
“…One study found that interview-based screening tools performed preoperatively in hospitalized TJA patients, including the Nutritional Risk Screening (NRS 2002), Mini Nutritional Assessment (MNA), and Short-Form Mini Nutritional Assessment (SF-MNA), were able to predict risks of prolonged hospitalization, delayed mobilization, quality of life, and adverse events postoperatively [37]. In particular, the MNA has been shown to have a significant association with serum albumin and increased length of stay [67].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, establishing routine pathways that enable the preoperative identification of malnourished or high-risk patients requires an interdisciplinary team, given the multifaceted nature of nutritional disorders 6 . Of note, frankly malnourished patients are those who are unable to achieve metabolic and nutrient requirements, resulting in clear deficiencies or compromised anthropometric measures 10,13 . However, another important patient subset may be "at nutritional risk," which is an abnormal metabolic state that can be detected and reversed preoperatively 10 .…”
Section: Preoperative Screening and Patient Optimizationmentioning
confidence: 99%
“…While a plethora of published literature describes post-TJA adverse outcomes associated with malnutrition, studies providing interventional recommendations for preoperative nutritional status correction are scarce. The tenet of nutritional-status optimization is the correction of underlying abnormalities through nutrient-specific supplementation to reverse deficiencies 5,10 . In addition, general nutritional supplementation may aid in mitigating the risk of adverse outcomes (Table V).…”
Section: Preoperative Screening and Patient Optimizationmentioning
confidence: 99%
See 2 more Smart Citations